Tissue Distribution and Abundance of the Parasitic Dinoflagellate Hematodinium perezi in Naturally Infected Portunus trituberculatus - Ju Zhang; Meng Li; Qian Huang; Lijun Hu; Qi Xue; Jiayi Wang; Caiwen Li (Pathogens)
The parasitic dinoflagellate Hematodinium is an infectious pathogen that causes severe enzootic in numerous economically important marine crustaceans worldwide. Previous research has focused on investigating the identification and life stages of Hematodinium parasites, while the parasite abundance and tissue proliferation process of Hematodinium in naturally infected crustacean hosts need to be further studied. In the present study, the tissue tropisms and intensity of H. perezi were investigated in the naturally infected Chinese swimming crabs Portunus trituberculatus by both the qualitative (hemolymph assay, histology) and quantitative analysis (cell count, quantitative PCR). The results showed that in P. trituberculatus with infection level I (4 ± 2 parasites in 200× microscopic field), filamentous trophonts were observed in the hemolymph and stomach tissues, with the average parasite number and ITS 1 copy number of H. perezi quantitatively detected in hemolymph (1.0 × 102 parasites/mL) and stomach tissues (1.7 × 103 cells/g), respectively. H. perezi trophonts were observed in the hemolymph (4.3 × 104 parasites/mL) and exhibited broad distribution in multiple tissues with its highest abundance of H. perezi in pereiopod muscles (1.1 × 104 cells/g) followed by that in stomach (4.8 × 103 cells/g) in P. trituberculatus with infection level II (80 ± 10 parasites in 200× microscopic field). In P. trituberculatus with infection level III (200 ± 35 parasites in 200× microscopic field), a high abundance of H. perezi sporoblasts was found in the hemolymph (3.1 × 107 parasites/mL) and all of the other examined tissues, with its highest abundance detected in pereiopod muscles (3.5 × 104 cells/g). In addition, the number of host’s hemocytes was significantly decreased during the Hematodinium infection. This study provides a comprehensive quantitative characterization of the tissue distribution and abundance of H. perezi in its natural crab host which will contribute to better understanding of the crustacean host–Hematodinium interactions.